Serotonin control of sleep-wake behavior - Monti, Jaime M. (Sleep medicine reviews, 2011)
Based on electrophysiological, neurochemical, genetic and neuropharmacological approaches, it is currently accepted that serotonin (5-HT) functions predominantly to promote wakefulness (W) and to inhibit REM (rapid eye movement) sleep (REMS). Yet, under certain circumstances the neurotransmitter contributes to the increase in sleep propensity. Most of the serotonergic innervation of the cerebral cortex, amygdala, basal forebrain (BFB), thalamus, preoptic and hypothalamic areas, raphe nuclei, locus coeruleus and pontine reticular formation comes from the dorsal raphe nucleus (DRN). The 5-HT receptors can be classified into at least seven classes, designated 5-HT 1–7. The 5-HT 1A and 5-HT 1B receptor subtypes are linked to the inhibition of adenylate cyclase, and their activation evokes a membrane hyperpolarization. The actions of the 5-HT 2A, 5-HT 2B and 5-HT 2C receptor subtypes are mediated by the activation of phospholipase C, with a resulting depolarization of the host cell. The 5-HT 3 receptor directly activates a 5-HT-gated cation channel which leads to the depolarization of monoaminergic, aminoacidergic and cholinergic cells. The primary signal transduction pathway of 5-HT 6 and 5-HT 7 receptors is the stimulation of adenylate cyclase which results in the depolarization of the follower neurons. Mutant mice that do not express 5-HT 1A or 5-HT 1B receptor exhibit greater amounts of REMS than their wild-type counterparts, which could be related to the absence of a postsynaptic inhibitory effect on REM-on neurons of the laterodorsal and pedunculopontine tegmental nuclei (LDT/PPT). 5-HT 2A and 5-HT 2C receptor knock-out mice show a significant increase of W and a reduction of slow wave sleep (SWS) which has been ascribed to the increase of catecholaminergic neurotransmission involving mainly the noradrenergic and dopaminergic systems. Sleep variables have been characterized, in addition, in 5-HT 7 receptor knock-out mice; the mutants spend less time in REMS that their wild-type counterparts. Direct infusion of the 5-HT 1A receptor agonists 8-OH-DPAT and flesinoxan into the DRN significantly enhances REMS in the rat. In contrast, microinjection of the 5-HT 1B (CP-94253), 5-HT 2A/2C (DOI), 5-HT 3 (m-chlorophenylbiguanide) and 5-HT 7 (LP-44) receptor agonists into the DRN induces a significant reduction of REMS. Systemic injection of full agonists at postsynaptic 5-HT 1A (8-OH-DPAT, flesinoxan), 5-HT 1B (CGS 12066B, CP-94235), 5-HT 2C (RO 60-0175), 5-HT 2A/2C (DOI, DOM), 5-HT 3 (m-chlorophenylbiguanide) and 5-HT 7 (LP-211) receptors increases W and reduces SWS and REMS. Of note, systemic administration of the 5-HT 2A/2C receptor antagonists ritanserin, ketanserin, ICI-170,809 or sertindole at the beginning of the light period has been shown to induce a significant increase of SWS and a reduction of REMS in the rat. Wakefulness was also diminished in most of these studies. Similar effects have been described following the injection of the selective 5-HT 2A receptor antagonists volinanserin and pruvanserin and of the 5-HT 2A receptor inverse agonist nelotanserin in rodents. In addition, the effects of these compounds have been studied on the sleep electroencephalogram of subjects with normal sleep. Their administration was followed by an increase of SWS and, in most instances, a reduction of REMS. The administration of ritanserin to poor sleepers, patients with chronic primary insomnia and psychiatric patients with a generalized anxiety disorder or a mood disorder caused a significant increase in SWS. The 5-HT 2A receptor inverse agonist APD-125 induced also an increase of SWS in patients with chronic primary insomnia. It is known that during the administration of benzodiazepine (BZD) hypnotics to patients with insomnia there is a further reduction of SWS and REMS, whereas both variables tend to remain decreased during the use of non-BZD derivatives (zolpidem, zopiclone, eszopiclone, zaleplon). Thus, the association of 5-HT 2A antagonists or 5-HT 2A inverse agonists with BZD and non-BZD hypnotics could be a valid alternative to normalize SWS in patients with primary or comorbid insomnia.